UTILITY OF INFLAMMATORY MARKERS FOR TOCILIZUMAB IN COVID-19 PATIENTS: A SINGLE-SITE RETROSPECTIVE STUDY - Amir, Muhammad; Ali, Usman; Javed, Adan; Ahmad, Jawad (Journal of Ayub Medical College Abbottabad, 2022)
Background: Studies are available on the use of inflammatory biomarkers for profiling and patient prognosis, but literature for tocilizumab monitoring parameters is scarce. Thus, we aim to evaluate different inflammatory markers that can relate to the effectiveness of tocilizumab in hospitalized patients suffering from severe covid. Method: We analyzed a retrospective cohort of 227 patients who were admitted due to SAR-Co2 in one of the largest hospitals in Pakistan, Lady Reading Hospital. Using in-hospital mortality as the primary parameter for the effectiveness of tocilizumab. Wilcoxon rank-sum test, chi-square test and ROC curve analysis were performed to evaluate inflammatory biomarkers. The p- values less than 0.05 were considered statistically significant. Result: A total of 1639 tests were identified from 227 patients admitted to the hospital. CRP (28%), LDH (27.3%) were the most commonly prescribed and 40% of the total test were prescribed pre-dose. D-dimer, ferritin and CRP were found to have a clinically significant impact of the dose. Conclusion: D-dimer, ferritin and LDH do not seem to relate proportionally with tocilizumab effectiveness. CRP can be utilized for monitoring tocilizumab effectiveness.